2017
DOI: 10.1002/2211-5463.12209
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating cell nuclear antigen restores the enzymatic activity of a DNA ligase I deficient in DNA binding

Abstract: Proliferating cell nuclear antigen (PCNA) coordinates multienzymatic reactions by interacting with a variety of protein partners. Family I DNA ligases are multidomain proteins involved in sealing of DNA nicks during Okazaki fragment maturation and DNA repair. The interaction of DNA ligases with the interdomain connector loop (IDCL) of PCNA through its PCNA‐interacting peptide (PIP box) is well studied but the role of the interacting surface between both proteins is not well characterized. In this work, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…After 15–30 min of phagocytosis, all four proteins appeared spread in the cytoplasm and in the membranes and lumen of phagosomes and surrounding the ingested erythrocytes (Figure 2C ). Intriguingly, EhVps24 and EhVps2, consistently migrated to the nuclei at longer times of phagocytosis (60 min), co-localizing with the nuclear protein pCNA (Trasviña-Arenas et al, 2017 ) and DAPI staining (Figures 2C,E ). Altogether, these results demonstrated that the ESCRT-III orthologs associate to erythrocytes and erythrocyte-containing phagosomes, suggesting that ESCRT-III proteins are a part of the machinery involved in phagocytosis.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…After 15–30 min of phagocytosis, all four proteins appeared spread in the cytoplasm and in the membranes and lumen of phagosomes and surrounding the ingested erythrocytes (Figure 2C ). Intriguingly, EhVps24 and EhVps2, consistently migrated to the nuclei at longer times of phagocytosis (60 min), co-localizing with the nuclear protein pCNA (Trasviña-Arenas et al, 2017 ) and DAPI staining (Figures 2C,E ). Altogether, these results demonstrated that the ESCRT-III orthologs associate to erythrocytes and erythrocyte-containing phagosomes, suggesting that ESCRT-III proteins are a part of the machinery involved in phagocytosis.…”
Section: Resultsmentioning
confidence: 81%
“…In the case of nuclear co-localization, rEhVps2 and EhVps24 were detected by secondary antibodies as described previously. pCNA (Trasviña-Arenas et al, 2017 ) protein was detected incubating cells with α-pCNA (Trasviña-Arenas et al, 2017 ) (1:200) for 1h at 37°C, followed by incubation with α-mouse TRITC-labeled antibodies (1:100) at 37°C for 1h. Nuclei were counterstained by 2.5 μg/ml 4′,6-diamidino-2-phenylindole (DAPI; Sigma) for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…In several systems, DNA ligase I is recruited to DNA damaged sites by its interaction with PCNA (Mortusewicz et al, 2006 ). Moreover, EhDNAligI activity is enhanced by EhPCNA and these proteins present a functional interaction in vitro (Cardona-Felix et al, 2011 ; Trasviña-Arenas et al, 2017 ). Thus, we tested whether during recovery from UV and H 2 O 2 treatments, EhDNAligI co-localizes with EhPCNA using an antibody generated against the rEhDNAligI recombinant protein (Cardona-Felix et al, 2010 , 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…At present, PCNA has been widely used in the study of cell proliferation kinetics [16]. In this study, we found that lung, liver and kidney cells proliferated to repair their corresponding organs after injury, but the duration of proliferation and degree of each organ were also different due to their differing abilities to self-repair and mechanism of each organ.…”
Section: Significance Of Apoptosis Proliferation and Inflammatory Famentioning
confidence: 78%